The molecular dimension of microbial species: 3. Comparative genomics of Synechococcus strains with different light responses and in situ diel transcription patterns of associated putative ecotypes in the Mushroom Spring microbial mat - Olsen, Millie T.; Nowack, Shane; Wood, Jason M.; Becraft, Eric D.; LaButti, Kurt; Lipzen, Anna; Martin, Joel; Schackwitz, Wendy S.; Rusch, Douglas B.; Cohan, Frederick M.; Bryant, Donald A.; Ward, David M. (Frontiers in Microbiology, 2015)
Genomes were obtained for three closely related strains of Synechococcus that are representative of putative ecotypes that predominate at different depths in the 1 mm-thick, upper-green layer in the 60°C mat of Mushroom Spring, Yellowstone National Park, and exhibit different light adaptation and acclimation responses. The genomes were compared to the published genome of a previously obtained, closely related strain from a neighboring spring, and differences in both gene content and orthologous gene alleles between high-light-adapted and low-light-adapted strains were identified. Evidence of genetic differences that relate to adaptation to light intensity and/or quality, CO2 uptake, nitrogen metabolism, organic carbon metabolism, and uptake of other nutrients were found between strains of the different putative ecotypes. In situ diel transcription patterns of genes, including genes unique to either low-light-adapted or high-light-adapted strains and different alleles of an orthologous photosystem gene, revealed that expression is fine-tuned to the different light environments experienced by ecotypes prevalent at various depths in the mat. This study suggests that strains of closely related putative ecotypes have different genomic adaptations that enable them to inhabit distinct ecological niches while living in close proximity within a microbial community.